English Noun Phrase Structure Found in Inclover Magazine - Kumbara Omar, Brama; Putu Intan Yuliana, Ni; Umiyati, Mirsa (KnE Social Sciences, 2022)
The aim of this paper was to know about English noun phrase, especially the types and structure of noun phrase. To collect the data, the data source was read carefully, then underlined, and quoted based on the types of them. They were analyzed qualitatively based on the theories. There are two theories that were used in this paper. First, the theory from book entitled A University Grammar of the English by Quirk and Greenbaum (1973) which discussed about the concept of the types of noun phrase structure and the tree diagram theory which is adopted from Richard Veit in his book Discovering English Grammar (1986). Based on the analysis, it was found that a lot of noun phrases occur in the magazine. The types of noun phrase were divided into three categories, they are pre-modification noun phrase, post-modification noun phrase and multiple modification noun phrase. The filler of the noun phrases was represented by the tree diagram that had shown more clearly explanation about the internal structures of the construction of the noun phrase. Keywords: noun phrase, modifiers, syntax